2022
DOI: 10.3389/fcell.2022.1061216
|View full text |Cite
|
Sign up to set email alerts
|

miR-1260b inhibits periodontal bone loss by targeting ATF6β mediated regulation of ER stress

Abstract: The expression profiles of exosomal microRNAs (miRNAs) are regulated by the microenvironment, and appropriate priming with mesenchymal stem cells (MSCs) is one of the strategies to enhance the paracrine potency of MSCs. Our previous work demonstrated that exosomes from tumor necrosis factor (TNF)-α-primed human gingiva-derived MSCs (GMSCs) could be a therapeutic tool against periodontitis, and that TNFα-inducible exosomal miR-1260b is essential for the inhibition of alveolar bone loss. However, the precise mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…found similar conclusions where PDLSC‐Exos alleviated an inflammatory microenvironment through the Th17/Treg/miR‐155‐5p/SIRT1 regulatory network, improving periodontitis. Two basic research studies also found that exosomes derived from separate sources were able to significantly decrease immune cell‐driven osteoclastogenesis and prevent bone loss 70,74 . Interestingly, Jarmalavičiūtė et al 64 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…found similar conclusions where PDLSC‐Exos alleviated an inflammatory microenvironment through the Th17/Treg/miR‐155‐5p/SIRT1 regulatory network, improving periodontitis. Two basic research studies also found that exosomes derived from separate sources were able to significantly decrease immune cell‐driven osteoclastogenesis and prevent bone loss 70,74 . Interestingly, Jarmalavičiūtė et al 64 .…”
Section: Resultsmentioning
confidence: 99%
“…A study by Zheng et al69 found similar conclusions where PDLSC-Exos alleviated an inflammatory microenvironment through the Th17/Treg/miR-155-5p/SIRT1 regulatory network, improving periodontitis. Two basic research studies also found that exosomes derived from separate sources were able to significantly decrease immune cell-driven osteoclastogenesis and prevent bone loss 70,74. Interestingly, Jarmalavičiūtė et al64 found that exosomes specifically (but not microvesicles) derived from SHEDs improved dopaminergic neurons by approximately 80%, suggesting that exosomes derived from SHEDs should be considered a new potential therapeutic tool in the treatment of Parkinson's disease.…”
mentioning
confidence: 99%
“…miR-487b-3p improves chemoresistance or metastasis in osteosarcoma but impairs osteoblastgenesis, and promotes tumorigenesis in colon cancer, prostate cancer and glioma (50)(51)(52)(53)(54). miR-1260b promotes tumorigenesis in breast cancer and lung adenocarcinoma and also inhibits bone loss (55)(56)(57). miR-4758-3p promotes tumorigenesis in glial tumor, gastric cancer and endometrial tumors (58-60), but its association with osteosarcoma is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…C57BL/6NCrSlc mice (female, 8-week-old) were purchased from Japan SLC (Hamamatsu, Japan) and used following the guidelines of an institutionally approved animal research protocol (protocol #A21-131-2; Kyushu University). After one week of quarantine and acclimation, ligature-induced periodontal mouse model was established as previously described [ 17 ]. Briefly, the mice were randomly classified into the following four groups with different treatments ( n = 6): (1) placebo (PBS), (2) DP-1-derived MVs, (3) luteolin-treated DP-1-derived MVs, and (4) LPS from E. coli or P. gingivalis .…”
Section: Methodsmentioning
confidence: 99%